2014
DOI: 10.1111/vop.12203
|View full text |Cite
|
Sign up to set email alerts
|

High incidence of spontaneous cataracts in aging laboratory rabbits of an inbred strain

Abstract: Objective To investigate the occurrence of spontaneous cataracts in a breeding colony of the inbred EIII/JC strain of New Zealand White rabbits (Oryctolagus cuniculi) and the congenic strain of EIII/JC-HLA-A2.1transgenic rabbits. Procedure A retrospective study was conducted by collecting and analyzing data from clinical records for individual rabbits filed between January 2011 and October 2013. Results Thirteen cases (8 females and 5 males) of cataract were identified in a group of 51 EIII/JC inbred rabbi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 17 publications
0
11
0
Order By: Relevance
“…The full pedigree involved 2,657 rabbits and 1,939 of them were inbred (73.0%) with inbreeding coefficients ranging from 4.5% to 68.1%. This population must be seen as an intermediate stage between standard commercial rabbit lines (Ragab, Sánchez, & Baselga, ) and laboratory strains (Peng, Roshwalb, Cooper, Zimmerman, & Christensen, ) in terms of accumulated inbreeding. The inbreeding coefficient must be appropriately decomposed to be implemented in the model outlined above.…”
Section: Resultsmentioning
confidence: 99%
“…The full pedigree involved 2,657 rabbits and 1,939 of them were inbred (73.0%) with inbreeding coefficients ranging from 4.5% to 68.1%. This population must be seen as an intermediate stage between standard commercial rabbit lines (Ragab, Sánchez, & Baselga, ) and laboratory strains (Peng, Roshwalb, Cooper, Zimmerman, & Christensen, ) in terms of accumulated inbreeding. The inbreeding coefficient must be appropriately decomposed to be implemented in the model outlined above.…”
Section: Resultsmentioning
confidence: 99%
“…18, 37, 38, 39, 40, 41 A third important aspect is the scarcity of inbred rabbit strains, while most mouse strains are inbred. 1, 42 It is thought that inbred strains in general elicit less diverse immune responses, which makes it more difficult to raise strong and diverse binders. 18 Correspondingly, in many IHC studies that compared rabbit and mouse mAbs to the same human antigens, rabbit mAbs consistently revealed higher sensitivity.…”
Section: Introductionmentioning
confidence: 99%
“…Rabbit cataracts have been described in association with Encephalitozoon cuniculi . One study also indicated that age‐related rabbit cataracts might develop due to inbreeding . However, there is very little published information about the behavioral and ocular health impact of cataracts and cataract surgery in pet rabbits.…”
Section: Introductionmentioning
confidence: 99%